A busca da “palavra perdida” no Brasil: Uma leitura de "Das Jahr Lazertis" de Günter Eich - Ribeiro de Sousa, Celeste H. M. Ribeiro (Contingentia, 2008)
In "Das Jahr Lazertis" Günter Eich works with the concept of “lost word” on multiple levels with mythological, historical, geographical, psychological, sociologic and poetical implications. This article pretends to investigate the textual constructions of these semantic configurations.